Evaluasi Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di SDN 14 Koto Panjang Pauh,Kota Padang - Shintia Saputri; Riani Sukma Wijaya (CV. ITTC INDONESIA, 2024)
School Operational Assistance Funds (BOS) is a government assistance program to provide initial non-personnel costs for educational units. The aim of this research is to evaluate the use, management and reporting of BOS funds. The research method used is a qualitative descriptive method. The data collection procedure uses interview methods and documentation.The results of this research show that (1) the use of BOS funds is in accordance with the BOS technical guidelines (2) Management of BOS funds is in accordance with the 2021 BOS technical guidelines and is open and involves the school principal as the main person responsible. (3) Reporting of BOS Funds is in accordance with the 2021 BOS technical guidelines. For proof of reporting for every purchase or expenditure, a note or receipt must be made in accordance with the RKAS that has been made.